2020 XXXV Conference on Design of Circuits and Integrated Systems (DCIS) 2020
DOI: 10.1109/dcis51330.2020.9268645
|View full text |Cite
|
Sign up to set email alerts
|

Developing an AI IoT application with open software on a RISC-V SoC

Abstract: RISC-V is an emergent architecture that is gaining strength in low-power IoT applications. The stabilization of the architectural extensions and the start of commercialization of RISC-V based SOCs, like the Kendryte K210, raises the question of whether this open standard will facilitate the development of applications in specific markets or not.In this paper we evaluate the development environments, the toolchain, the debugging processes related to the Sipeed MAIX Go development board, as well as the standalon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…The work of [31] uses a Universal Sensor Platform (USeP) SoC to meet the requirements imposed by IoT, which features a RISC-V processor and integrates a range of peripherals with a scalable subsystem as a Three Dimensional System-in-Package (3D-SiP). Further, the Sipeed MAIX-Go development board employed by [66] features a Kendryte SoC K210, with a dual-core 64-bit RISC-V with the RV64GC ISA, including an Floating-Point Unit (FPU) compliant with support to single and double-precision multiply, divide, and square-root operations.…”
Section: B Soc Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of [31] uses a Universal Sensor Platform (USeP) SoC to meet the requirements imposed by IoT, which features a RISC-V processor and integrates a range of peripherals with a scalable subsystem as a Three Dimensional System-in-Package (3D-SiP). Further, the Sipeed MAIX-Go development board employed by [66] features a Kendryte SoC K210, with a dual-core 64-bit RISC-V with the RV64GC ISA, including an Floating-Point Unit (FPU) compliant with support to single and double-precision multiply, divide, and square-root operations.…”
Section: B Soc Platformsmentioning
confidence: 99%
“…Torres-Snchez et al [66] evaluate the development environment toolchains and debugging process concerning the Sipeed MAIX Go development board and Tiny YOLO v2 support by deploying a low-power IoT edge application, achieving good performance and cost characteristics.…”
Section: ) Development Toolsmentioning
confidence: 99%
“…There are a number of works using edge AI devices for various practical applications, such as face mask detection [9], resilient image compression for IoT cameras [10], mineral granulometric analysis [11], conveyor belt longitudinal rip detection [12]. Most of the work focuses on the problems of image analysis.…”
Section: Edge Neural Network Computingmentioning
confidence: 99%
“…Bailey et al [16] demonstrated a signal analysis SoC consisting of a general-purpose RISC-V core with vector extensions and a fixed-function signal-processing accelerator. Enrique et al [17] used open-source software to develop AI IoT applications on RISC-V SoC. The advantages of the RISC-V architecture in security and power consumption promote the application of RISC-V in the Internet of Things (IoT), mobile terminal, edge computing, and other fields.…”
Section: Introductionmentioning
confidence: 99%